PRINSIP KEHATI-HATIAN BAGI NOTARIS/PPAT DALAM MENJALANKAN TUPOKSINYA DALAM UPAYA PENCEGAHAN KRIMINALISASI BERDASARKAN KODE ETIK - Denny Saputra; Sri Endah Wahyuningsih (Jurnal Akta, 2017)
This study aims to determine 1) how the precautionary principle for Notary / PPAT in carrying out its position in prevention of criminalization based on Code of Conduct, 2) What factors become obstacles for Notary / PPAT in carrying out its position and 3) What if Notary / PPAT is subject to Code violation until criminalization occurs The problem approach used is the normative juridical approach.The result of this research is that the precautionary principle for Notary / PPAT in carrying out its position in prevention of criminalization based on code of ethics that a Notary must always implement the principle of prudence as an effort to prevent criminalization based on code of ethics related to responsibility both civil, Administration, code of ethics of notary and criminal law, then the factors that become obstacle for Notary / PPAT in carrying out their position related to the principle of prudence is the information given by the parties that facing may not be in accordance with the actual and Notary / PPAT in running His duties and positions are subservient to the NOtaris Office Law. Therefore, if a Notary commits an offense in performing his duties and positions, until the criminalization of Notary is threatened with sanctions as stated in UUJN. Sanctions against a Notary are categorized into 2 (two), namely civil sanction in the form of reimbursement of costs, compensation, and interest is the result that will be received by Notary on the demands of the tapers if the deed concerned only has the power of proof as deed under the hand or deed becomes null for the sake of law. Notary also still have to face the threat of sanction in the form of ethical sanction if Notary do violation to code of ethic of Notary, and even can be sentenced to criminal sanction in case of criminal violationKeywords: Notary, Prudential Principle